2004
DOI: 10.1162/0898929042947865
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Modulation of Amygdala Responsivity to Surprised Faces

Abstract: We recently demonstrated a functional relationship between fMRI responses within the amygdala and the medial prefrontal cortex based upon whether subjects interpreted surprised facial expressions positively or negatively. In the present fMRI study, we sought to assess amygdala-medial prefrontal cortex responsivity when the interpretations of surprised faces were determined by contextual experimental stimuli, rather than subjective judgment. Subjects passively viewed individual presentations of surprised faces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

33
277
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 365 publications
(316 citation statements)
references
References 108 publications
33
277
1
5
Order By: Relevance
“…In the present study, a basic correlational analysis (averaging across the time series for each event type) indicated a substantial extent of covariation between regions associated with controlled processing (VLPFC and OFC) and those associated with task-related processing (PPA), as well as a relationship between OFC and amygdala activity during trials with negative distractors potentially reflecting inhibitory connections (Kim et al, 2004;Logothetis, 2003). More advanced functional connectivity analyses have been used successfully in two recent studies of 5HTT-LPR genotype effects on prefrontal and limbic activation in affective processing paradigms (Heinz et al, 2005;Pezawas et al, 2005).…”
Section: Discussionsupporting
confidence: 47%
“…In the present study, a basic correlational analysis (averaging across the time series for each event type) indicated a substantial extent of covariation between regions associated with controlled processing (VLPFC and OFC) and those associated with task-related processing (PPA), as well as a relationship between OFC and amygdala activity during trials with negative distractors potentially reflecting inhibitory connections (Kim et al, 2004;Logothetis, 2003). More advanced functional connectivity analyses have been used successfully in two recent studies of 5HTT-LPR genotype effects on prefrontal and limbic activation in affective processing paradigms (Heinz et al, 2005;Pezawas et al, 2005).…”
Section: Discussionsupporting
confidence: 47%
“…Although amygdala processing has been shown to occur rapidly and unconsciously, these data add to the growing evidence that goals may modulate amygdala activation to generate contextually appropriate and nuanced evaluations (Kim et al, 2004). Although complex neural networks play an important role in rendering an evaluation, we suggest that flexibility may be a core operating characteristic of specific components within these networks.…”
Section: Discussionmentioning
confidence: 69%
“…While the amygdala and/or other cortical and subcortical structures could be more relevant in the analysis of face appearance (Tamietto et al, 2005), the dmPFC is likely to intervene at a later stage, combining face appearance with available information about the agent's behavior (Baron et al, 2011; see also Costa et al, 2013). Accordingly, it has been suggested that the dmPFC works as a convergence area for face and behavioral information, interacting with the amygdala's signals (Baron et al, 2011;Kim et al, 2004). In light of this, we cannot exclude that TMS had indirectly affected the amygdala as well as other cortical or subcortical regions, such as the anterior cingulate cortex (important in conflict monitoring; see Botvinick, Braver, Barch, Carter, & Cohen, 2001), and the orbitofrontal cortex (important in processing of positive/rewarding stimuli, e.g., Blair et al, 2013;O'Doherty, Kringelbach, Rolls, Hornak, & Andrews, 2001;Rolls, 2000).…”
Section: Discussionmentioning
confidence: 99%